2017
DOI: 10.1007/s12975-017-0596-5
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Splenic Contraction and the Systemic Inflammatory Response After Acute Ischemic Stroke Varies with Age and Race

Abstract: Animal models have demonstrated the deleterious contribution of splenic immunocytes on secondary brain injury after stroke. While previous work has demonstrated splenic contraction (SC) in patients with acute ischemic stroke (AIS) and intracranial hemorrhage (ICH), no clinical studies have examined the relationship between the systemic inflammatory response syndrome (SIRS) with SC in stroke patients. This is a retrospective analysis of a previous prospective observational study where daily spleen sizes were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 45 publications
(63 reference statements)
2
20
0
Order By: Relevance
“…In Alicia's study, 69.2% of patients were posterior circulation stroke, which was the heat-regulating centers located in. In terms of the time of occurrence, we found that most cases of SIRS (95.7%) occurred in the rst two days after EVT, which was consistent with the results of a previous study found that 79.1% of SIRS cases presented within 72 h after stroke [16]. A recently published study from Stanford used a single-cell mass cytometry approach to observe the systemic immune response to stroke in longitudinal blood samples from 24 patients over the course of 1 year and suggested the rst 2 days as the acute phase of in ammation [17].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In Alicia's study, 69.2% of patients were posterior circulation stroke, which was the heat-regulating centers located in. In terms of the time of occurrence, we found that most cases of SIRS (95.7%) occurred in the rst two days after EVT, which was consistent with the results of a previous study found that 79.1% of SIRS cases presented within 72 h after stroke [16]. A recently published study from Stanford used a single-cell mass cytometry approach to observe the systemic immune response to stroke in longitudinal blood samples from 24 patients over the course of 1 year and suggested the rst 2 days as the acute phase of in ammation [17].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies aiming to elucidate the prevalence of SIRS have shown that approximately 18-53% of ischemic stroke patients experience SIRS in hospital [6,7,16], Boehme et al [7] found about 20% of stroke patients treated with rt-PA developed SIRS, and the presence of SIRS was positively related to initial stroke severity and poor short-term functional outcomes. However, the outcomes of SIRS in patients after EVT remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In individuals over the age of 75, there was a negative correlation with splenic contraction and the development of SIRS at 72 h post stroke, while there was no significant connection between splenic contraction and SIRS in the younger age groups. In stroke subjects over the age of 75, the development of SIRS was higher in individuals without splenic contraction compared to those subjects with splenic contraction (71.4 vs. 46.1, respectively) [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interferon gamma (IFNγ) production by T cells and natural killer (NK) cells and subsequent induction of interferon inducible protein 10 (IP-10) triggers the first step in the delayed inflammatory response [ 26 , 28 30 ]. Clinical data have shown that this post-stroke splenic response not only occurs in human stroke patients, but also differs among patients of different ages and racial backgrounds [ 31 33 ].…”
Section: Introductionmentioning
confidence: 99%